2010
DOI: 10.1093/hmg/ddq061
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale genomic studies reveal central role of ABO in sP-selectin and sICAM-1 levels

Abstract: P-selectin and intercellular adhesion molecule-1 (ICAM-1) participate in inflammatory processes by promoting adhesion of leukocytes to vascular wall endothelium. Their soluble levels have been associated with adverse cardiovascular events. To identify loci affecting soluble levels of P-selectin (sP-selectin) and ICAM-1 (sICAM-1), we performed a genome-wide association study in a sample of 4115 (sP-selectin) and 9813 (sICAM-1) individuals of European ancestry as a part of The Cohorts for Heart and Aging Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
245
2
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(267 citation statements)
references
References 58 publications
11
245
2
9
Order By: Relevance
“…Previous studies reported that blood group A may influence the systemic inflammatory response as they found associations between the genotype of the A blood group antigen and circulating levels of soluble intercellular adhesion molecule 1, E-selection and P Selection suggesting that [44,45]. These may resulted in the increased incidence of breast cancer in blood type A cases.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies reported that blood group A may influence the systemic inflammatory response as they found associations between the genotype of the A blood group antigen and circulating levels of soluble intercellular adhesion molecule 1, E-selection and P Selection suggesting that [44,45]. These may resulted in the increased incidence of breast cancer in blood type A cases.…”
Section: Discussionmentioning
confidence: 98%
“…Modified expression of blood group antigens on the surface of cancer cells may alter cell motility, sensitivity to apoptosis and immune escape, and thus influence the initiation and spread of cancer (Le Pendu et al, 2001). In addition, recent studies have reported associations between ABO blood groups and circulating levels of tumor necrosis factor-alpha and soluble ICAM-1, E-selectin and P-selectin (Melzer et al, 2008;Paterson et al, 2009;Barbalic et al, 2010;Qi et al, 2010), suggesting that blood group antigens may influence the systemic inflammatory response. Chronic inflammation has been extensively linked with cancer development (Grivennikov et al, 2010), and provides a further potential mechanism by which ABO antigens may influence cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…29 In addition, the ABO blood groups have been associated with plasma soluble intercellular adhesion molecule 1 (ICAM-1) and TNF receptor 2 (TNF-R2) levels. 30 These markers have both been associated with an increased type 2 diabetes risk, thus providing a potential explanation for the observed relationships. 31,32 Finally, a recent paper suggested that the ABO blood group is one of the genetically determined host factors that modulate the composition of the intestinal microbiota 33 which participates in metabolism by affecting the energy balance, glucose metabolism and low-grade inflammation.…”
Section: Discussionmentioning
confidence: 97%